If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 7x + -5x = -21 Combine like terms: 7x + -5x = 2x 1 + 2x = -21 Solving 1 + 2x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = -21 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = -21 + -1 2x = -21 + -1 Combine like terms: -21 + -1 = -22 2x = -22 Divide each side by '2'. x = -11 Simplifying x = -11
| 3(2x-1)+2=5x | | 5a-7=18 | | 0.556(r)+25=-25 | | X-11=-11 | | -x+9+3x=33 | | 5y(-9-3y)=13 | | 0.4(t)-4=2 | | 0.7x+0.38=0.645 | | y=2x^2+6x-108 | | k-5=15 | | 8(x-2)-6x=12-(8x-7) | | s*s=25 | | 3n+5=23 | | -4=6x-5x+4 | | 3x+9=180 | | 2x-18=-6 | | 8x+4(6-x)=2x-16 | | 2x-7y=33 | | 6+7x-5x=16 | | 2-7y=6 | | x+2x=-9 | | x+x*2x=-9 | | 5x+10+6x=10 | | 6x-5=3x+9 | | a+4a=96+a | | 149-5x=22x+20 | | 5(f+2)=2(3-5) | | 4(5a+2)=12(a-1) | | 3-4x+5x=2 | | 3x+33=11x-31 | | 3x(2x-7)-2x(x+3)= | | 5b-28=22 |